Register in Reviewing Indonesian Food in Marina Tasha’s YouTube Vlog: Sociolinguistics Study - Azzahra, Salsabila Shafa; Simatupang, Ervina CM (Universitas Cokroaminoto Palopo, 2024)
This research, titled